INTEGRASI GREEN FINANCE TERHADAP NILAI PERUSAHAAN : PERSPEKTIF SEKTOR PERBANKAN DI INDONESIA - Ningsi, Etty Harya; Manurung, Lambok; Rizki, Mela Novita (JEBIM Prima, 2024)
In a business context, the concept of sustainability leads to the development of socially and environmentally responsible business practices, including efficient use of resources, responsible management of waste and emissions, protection of human rights, and involvement in sustainability initiatives and programs. The purpose of this study is to determine the effect of integrating green finance on firm value in the banking sector in Indonesia. The research object used in this study is a banking company listed on the Indonesia Stock Exchange for the 2020-2022 period. In this study, it was found that there were 46 banking companies listed on the Indonesia Stock Exchange, but not all of these companies were sampled. Multiple linear regression analysis is an analysis used to see the effect of the independent variables on the dependent variable. This analysis also provides an overview of the direction of the relationship between the dependent variable and the independent variable. This study shows the results that the majority have no significant effect and also based on the discussion of this study it can be concluded that the integration of green finance does not have a significant effect on firm value so that the results of this test are not in accordance with the first hypothesis which assumes that the integration of green finance has a positive effect to company value.